Cronologia della letteratura rumena moderna (1780-1914) - Cronologia literaturii române moderne (1780-1914) - Angela Tarantino (Strumenti per la didattica e la ricerca, 2019)
Cronologia della letteratura rumena moderna (1780-1914) is intended for use as an interdisciplinary support, primarily for the students enrolled in Romanian Literature university courses. The volume aims at simplifying the search for information relating to literary history of nineteenth-century Romania, starting from the authors of the early modern age, therefore from the late Enlightenment period to World War I.